Khemmarat Wound Chair, an Innovation to Improve Wound Dressing Service - Pitichockphokin, Juckrapong; Pitichockphokin, Nunnaphas; Juengmankong, Baisri (Journal of Health Science of Thailand, 2017)
Emergency & Accident Department of Khemmarat Hospital, Ubonratchathani Province has been providing 24-hour services to patients who are in need of emergency medical care. The most common service for the years 2010 – 2012 is wound dressings with up to 50 cases per day, of whom around 10 cases were on wheelchair and had difficulty to be transferred to a hospital bed. The objective of this study was to invent a set of wound chair and utilize it to facilitate and improve performance of the wound dressing services. The research and development process began by creating a prototype model which was subsequently improved to make it practical and suitable for routine use in emergency rooms. The innovation was then tested with patients who had traumatic wounds or ulcers at the leg or foot areas and attended the emergency room in the fiscal year 2013. Data on service providers’ and patients’ satisfaction were collected through 20 participating physicians, emergency medical technician, and nurse aids; and assessment of the quality of care was also recorded. Data were analyzed using the number, percentage and means. It was found that there were 368 cases receiving the wound dressing services. The Khemmarat wound chair set had made wound dressing more easy, convenient and safe. There was no incidence of any complication (slippage or fall) during dressing. The equipment could be easily cleaned and stored. Staff satisfaction level was 95.0%, and that of patients and relative was 100.0%. With the cost of baht 500 (comparing to baht 4,800 for manufactured chair), the invented wound chair would help saving the baht 98,000 cost of an emergency room staff who would have been needed to move and hold the patients during wound dressing. Thus it was concluded that the Khemmarat Wound Chair is useful to improve the quality of care; and it should be widely promoted in other similar medical care settings.